Exploring the Shared Experiences of Yazidis Who Survived Genocide. Issue 4 (8th August 2022) - Cook, Wendy; Kennedy, Tom D.; Chenail, Ron; Detullio, David; Edmonds, W. Alex
ABSTRACT: In August 2014, the Islamic State of Iraq (ISIS) and the Levant (ISIL) brutally attacked the Yazidi people and occupied Sinjar and other villages in Northern Iraq. The massacre of Yazidis that began in August 2014 was declared by the United Nations as genocide. To gain a better understanding and raise awareness of these atrocities, we conducted a qualitative, phenomenological study with 35 Yazidis, who survived the genocide. The aim of the study was to elucidate the Yazidis' processing of the genocide and how it affects their psychological functioning. Coding and theming were the methods used to categorize, bring meaning and identity to Yazidis'genocidal experiences. The interviews took place between April and June 2019. Data analysis of the interview transcripts revealed that Yazidis, who survived the genocide of 2014, commonly experienced 11 themes related to hopelessness, fear, loss, grief, distrust, change, advocacy, optimism, shock, intrusive memories, and guilt. Results from this study reveal the vulnerabilities of ethnic minorities at risk of being abducted, killed, raped, and displaced. Moreover, the inherent risk of future genocides is illustrated through the experiences shared by the Yazidis.